Evaluation of Selected Synthetic and Botanical Insecticides against Tuta absoluta (Lepidoptera: Gelechiidae) under Field Conditions - Mangrio, Ghulam Qader; Gilal, Arfan Ahmed; Rajput, Lubna; Hajano, Jamal-U-Ddin; Panhwar, Zakia; Kubar, Muhammad Ibrahim; Koondhar, Naimatullah; Gabol, Abdul Hayee (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The invasive tomato leafminer Tuta absoluta has recently caused heavy losses to tomato growing areas around the world including Pakistan. Considering its significant damage potential, it is essential to conduct experiments using locally available botanicals and synthetic insecticides. Therefore, studies were conducted at a farmer’s field in the district Shaheed Benazir Abad, Sindh, Pakistan during complete tomato season of 2023-24. Synthetic insecticides, i.e., Tracer 450SC ® (Spinosad 480 g/L), Belt 480 SC ® (Flubendiamide 480 g/L), Novastar 56EC ® (Bifenthrin 5%+ Abamectin 0.6%), Talstar 10EC ® (Bifenthrin), and Trigard 750 g/kg ® (Cyromazine) and botanical insecticides, i.e., Neem (Azadirachta indica A. Juss.), Tobacco (Nicotiana tabacum L.), Datura, (Datura stramonium L.), Peppermint (Mentha piperita L.), and Eucalyptus (Eucalyptus camaldulensis Dehn.), along with untreated control were evaluated against T. absoluta During both sprays, synthetic insecticides were found to be comparatively more effective than botanicals, with Flubendiamide and Spinosad being the two most effective insecticides. The effectiveness of all insecticides was comparatively better in the second spray than first spray. After one week of the two sprays, the maximum infestation reduction on tomato leaves and fruits was recorded with Flubendiamide (73.34% and 85.60%, respectively), followed by Spinosad (70.58% and 83.57%, respectively), whereas Eucalyptus and Datura were the least effective insecticides. Among botanicals, Neem resulted in a maximum corrected reduction in T. absoluta infestation on tomato leaves (52.33%) and fruits (55.20%). Due to the effectiveness of insecticides in reducing T. absoluta infestation, a significant effect on tomato fruit yield was also observed as maximum yield was recorded with Flubendiamide (433.40 ± 5.46 maunds per acre) and Spinosad (420.80 ± 3.20 maunds per acre) treatments, whereas neem (389.60 ± 4.86 maunds per acre) gave maximum yield among botanicals. Therefore, it is recommended that due to the better performance of Flubendiamide and Spinosad, they should be included in the integrated management of T. absoluta infestation in tomatoes, whereas Neem can also be used as botanical insecticide due to its effectiveness against it.